Fast liquid crystal light shutter with polymer stabilisation. (2nd August 2021) - Hegde, Gurumurthy; Barbero, Giovanni; Komitov, Lachezar
Abstract: We present a fast-switching liquid crystal device comprising fringe field switching (FFS) electrode structure deposited onto one of the device substrates. Initially, the liquid crystal in the device has a homeotropic alignment. The generated periodic electric field by the FFS electrode results in a periodic splay/bend elastic deformation, thus giving rise to flexoelectric polarization along the substrate normal. At low applied voltages, this periodic elastic deformation, is substantially localized in a very thin portion of the liquid crystal layer adjacent to the substrate surface bearing the electrode and it is stabilized by a polymer network. Thus, the flexoelectric polarization becomes permanently present in the device and has non-zero value at field-off state. The polymer network with splay/bend configuration occupies very small part of the liquid crystal layer (∼0.5 μ m), which is thinner than the light wavelength and therefore is optically invisible. Simultaneously with the formation of the polymer network, possessing splay/bend configuration, a polymer network with polymeric bundles oriented preferably along the substrates' normal is formed. As we will show, the presence of the polymer network, consisting of surface and bulk parts, reduces substantially the switching times of the liquid crystal device more than one order bringing them to μ s range.